The association of catestatin and endocan with the effects of cardiac shock wave therapy: Biomarker sub-study of the randomized, sham procedure-controlled trial - Burneikaitė, Greta; Shkolnik, Evgeny; Puronaitė, Roma; Zuozienė, Gitana; Petrauskienė, Birutė; Misonis, Nerijus; Kazėnaitė, Edita; Laucevičius, Aleksandras; Smih, Fatima; Rouet, Philippe; Čelutkienė, Jelena (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Cardiac shock-wave therapy (CSWT) is a non-invasive regenerative treatment method based on low-frequency ultrasound waves, which stimulate angiogenesis. Recently, an association of catestatin and endocan with coronary collateral development was shown in several trials. In this study, we aimed to evaluate the impact of CSWT on the dynamics of catestatin and endocan levels and to assess their correlation with myocardial perfusion and function parameters. Methods: Prospective, randomized, triple-blind, sham procedure-controlled study enrolled 72 subjects who complied with defined inclusion criteria (NCT02339454). We measured biomarkers in 48 patients with stable angina (24 patients of CSWT group, 24 patients of sham-procedure group). Additionally, patients were divided into responders and non-responders according to improvement in myocardial perfusion and/or contractility assessed by myocardial scintigraphy and dobutamine echocardiography (30 and 13 patients, respectively). The blood samples were collected at baseline, after the last treatment procedure (9th treatment week) and at 6-month follow-up and stored at −80°C until analysis. Serum catestatin and endocan levels were determined by commercially available ELISA kits. Results: Serum catestatin concentration significantly increased in all patients. While endocan levels significantly decreased in the responders sub-group. The increase in catestatin levels at 9th week and 6-months was positively associated with improvement in summed difference score (rho=0.356, p=0.028) and wall motion score, WMS (rho=0.397, p=0.009) at 6-months in the whole study population. Meanwhile, the decrease in endocan levels over 6 months was positively correlated with improvement in WMS at 3- and 6-months (r=0.378, p=0.015 and r=0.311, p=0.045, respectively). ROC analysis revealed that a change at 6-months in catestatin and endocan levels significantly predicted improvement in myocardial perfusion and contractile function with 68.9% sensitivity and 75.0% specificity (p=0.039) and 51.7% sensitivity, and 91.7% specificity (p=0.017), respectively. Baseline endocan concentration and its change at 6-months predicted response to CSWT with 68.8% sensitivity and 83.3% specificity (p=0.039) and 81.3% sensitivity and 100% specificity (p<0.0001), respectively. Conclusion: This study demonstrates the association of increase in catestatin and decrease in endocan levels with the improvement of myocardial perfusion and contractile function. The potential predictive value of catestatin and endocan dynamics for the response to regenerative therapy is shown.